2021
DOI: 10.1186/s12879-021-06470-4
|View full text |Cite
|
Sign up to set email alerts
|

Interleukin 6 as a marker of severe bacterial infection in children with sickle cell disease and fever: a case–control study

Abstract: Background Etiological diagnosis of fever in children with sickle cell disease (SCD) is often challenging. The aim of this study was to analyze the pattern of inflammatory biomarkers in SCD febrile children and controls, in order to determine predictors of severe bacterial infection (SBI). Methods A prospective, case–control study was carried out during 3 years, including patients younger than 18 years with SCD and fever (cases) and asymptomatic st… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
5
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 32 publications
1
5
0
Order By: Relevance
“…Most children included in this study had been diagnosed by newborn screening, were completely immunized and receiving penicillin prophylaxis. We found a low rate of CSBI, with a higher proportion of PSBI (mainly pneumonia/ACS), in agreement to other studies from high-income countries [1,3,6]. Several studies had previously reported different predictors of bacteremia and other severe infections in patients with SCD, including elevated CRP, procalcitonin, WBC and neutrophils, toxic appearance, vomiting and longterm CVC, similarly to our findings [2,4,7,8].…”
Section: Discussionsupporting
confidence: 92%
“…Most children included in this study had been diagnosed by newborn screening, were completely immunized and receiving penicillin prophylaxis. We found a low rate of CSBI, with a higher proportion of PSBI (mainly pneumonia/ACS), in agreement to other studies from high-income countries [1,3,6]. Several studies had previously reported different predictors of bacteremia and other severe infections in patients with SCD, including elevated CRP, procalcitonin, WBC and neutrophils, toxic appearance, vomiting and longterm CVC, similarly to our findings [2,4,7,8].…”
Section: Discussionsupporting
confidence: 92%
“…TNF- is crucial to understanding the pathogenesis of RA. The expression of serum TNF- may make early RA more inflammatory [ 147 ]. As a result, it is necessary to test patients with RA for this cytokine to keep track of disease activity, which may be helpful for patients who are undergoing anti-TNF therapy.…”
Section: Discussionmentioning
confidence: 99%
“… 22 Early elevation of IL-6 in the presence of SBI, is an important advantage of this cytokine compared with other biomarkers. 23 IL-6 plays a significant role in inducing CRP and fibrinogen synthesis in the liver during bacterial infection.…”
Section: Existing Biomarkers In Ra With Infectionmentioning
confidence: 99%
“…The expression of serum TNF-α may enhance the inflammatory activity of early RA. 23 Therefore, RA patients must be screened for this cytokine to monitor disease activity, which may be useful in patients receiving anti-TNF therapy. TNF-α itself is a potent inducer of other proinflammatory cytokines and chemokines, further enhancing the inflammatory response.…”
Section: Existing Biomarkers In Ra With Infectionmentioning
confidence: 99%